Handing-over Notes from Mr. I.F.W. Schofield District Officer, to Mr. M.H.W. Swabey, District Officer Bamenda Division (Colonial Letters and the Contact of Knowledges, 1937)
This file contains colonial letters on handing over note by Schofield
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Handover Note; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies